The impact of valproic acid and 2-propyl-4-pentenoic acid on antioxidant status measured by GSH/GSSG ratio and FRAP levels in acute and chronic exposure - Karina Sommerfeld-Klatta; Magdalena Łukasik-Głębocka; Sylwia Kobyłka; Barbara Zielińska-Psuja (Polskie Towarzystwo Farmaceutyczne, 2023)
Valproic acid (VPA) is a broad-spectrum anticonvulsant drug. Its mechanism of action includes enhancing GABAergic transmission, blocking voltage-gated sodium channels, and affecting dopaminergic and serotonergic transmission (1). The mechanism of VPA toxicity, including its effects on the liver, is not fully known. It is assumed that oxidative stress and/or reactive products of drug biotransformation are responsible for its hepatotoxicity (2). The aim of the study was to verify the hypothesis concerning the influence of valproic acid and its metabolite, 2-propyl-4-pentenoic acid (4-en VPA) on the antioxidant status of patients treated with (VPA-T) and poisoned with valproic acid (VPA-P). The VPA-P group was divided into patients with (VPA-Ptox) and without (VPA-Pnon) toxic symptoms observed during the hospitalization. Oxidative stress was assessed using markers, such as antioxidant potential (FRAP) and reduced and oxidised glutathione (GSH/GSSG) ratio were measured in the plasma of the study patients. The obtained results showed statistically significant differences between the concentrations of the drug and its active metabolite levels in the VPA-T and VPA-P groups. In the VPA-P group, the increase of the level of 4-en VPA in the plasma correlated with the increase of the concentration of the drug. The influence of VPA on the antioxidant balance in both groups of patients was demonstrated. The plasma antioxidant potential of FRAP decreased with increasing valproic acid concentrations in the VPA-Ptox group. The lowest concentrations of GSH/GSSG ratio were found in the VPA-Pnon group, without symptoms of intoxication during hospitalization.